2004
DOI: 10.1111/j.1540-8159.2004.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Signal Amplitude Measurements in VDD Systems According to Body Position

Abstract: Single lead VDD pacing is an established therapy in patients with AV block. Body position may influence the amplitude of the atrial signal recorded through the floating atrial electrode. This study analyzed the degree of posture related variation in the signal amplitude of floating atrial electrodes in 63 patients (mean age 72 +/- 21 years) implanted with a VDD system. The average atrial amplitude in the supine position was 1.59 +/- 1.15 mV and decreased significantly in the sitting position (1.37 +/- 1.08, P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Another potential limitation is that P‐wave amplitude measurements were obtained at nighttime between 12 am and 2 am, most likely in a recumbent position. Previous studies using VDD pacemakers showed significant fluctuation of atrial signal with different body positions . However, a recent study using the DX ICD system found comparable range of atrial signal amplitude during various body postures …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another potential limitation is that P‐wave amplitude measurements were obtained at nighttime between 12 am and 2 am, most likely in a recumbent position. Previous studies using VDD pacemakers showed significant fluctuation of atrial signal with different body positions . However, a recent study using the DX ICD system found comparable range of atrial signal amplitude during various body postures …”
Section: Discussionmentioning
confidence: 91%
“…Previous studies using VDD pacemakers showed significant fluctuation of atrial signal with different body positions. 24,25 However, a recent study using the DX ICD system found comparable range of atrial signal amplitude during various body postures. 17…”
Section: Study Limitationsmentioning
confidence: 97%
“…21 The incidence of atrial undersensing in VDD systems is between 5% and 7% but is clinically silent in the vast majority of patients. [23][24][25] During follow-up, the amplified atrial sensing signal remained stable and showed no tendency for deterioration in the Aϩ-ICD group. The processing of the atrial signal differs between VDD pacemakers and the studied ICD, because the latter comprises a special input stage that amplifies the atrial signal up to 4-fold.…”
Section: Difference To Vdd Pacemaker Sensing Algorithmsmentioning
confidence: 94%
“…The reliability of this pacing system has been demonstrated in several studies 9,11,12,14,15 . However, due to a great variation of the atrial potential received by free‐floating electrodes 16 and instability of atrial dipole during changes in posture, 17,18 intermittent atrial undersensing remains a potential problem in single‐lead VDD pacing. Many studies have tried to define the predictors of long‐term failure of VDD pacing and to test the effects of new sensing algorithm and dipole design on the incidence of atrial undersensing 5,6 .…”
Section: Discussionmentioning
confidence: 99%